THE EXTENT OF PUBLIC RELATIONS RELIANCE ON THE USE OF ONLINE NEWSPAPERS IN ELECTION CAMPAIGNS - RAMADHAN, DR. OMARAHMED; MARIF, CHRO SHIAHAB (Journal of Duhok University, 2019)
This research is aimed to explore the public relation’ extent to recruit electronic newspaper in election campaigns. As well as to explore its effects. For reaching this goal the research used analytical survey method through questionnaire alongside with following statistic tools and examine Interconnectivity between research sample which are the employees and head of political parties election offices, 140 participants between male and female, chosen by Preview of intentional randomization method. The research concludes the following outcomes: The political parties’ public relation administrators initially and mainly depending on electronic newspapers during election campaigns. The research proves the alternative hypothesis, which points out that there is the linkage relationship of statistical significance between PR worker’s demographic variable in public relations and depending on electronic newspapers in election campaigns. The research proves the alternative hypothesis that there is the positive correlation relationship is a significant function between relying on electronic newspaper in election campaigns and motivation while that depending. There are some recommendations as follows: As long as that the electronic newspaper is one of the main tools that public relation depends on in election campaigns. There is a necessity to organize the election campaigns more systematically in order to archive selected objectives. Take advantage of this research’s achievements and focus on research on audiences.